2011
DOI: 10.1182/blood-2010-09-303081
|View full text |Cite
|
Sign up to set email alerts
|

Development of IL-22–producing NK lineage cells from umbilical cord blood hematopoietic stem cells in the absence of secondary lymphoid tissue

Abstract: Human secondary lymphoid tissues (SLTs) contain interleukin-22 (IL-22)-producing cells with an immature NK phenotype. Given their location, these cells are difficult to study. We have generated large numbers of NK22 cells from hematopoietic stem cells. HSC-derived NK22 cells show a CD56(+)CD117(high)CD94(-) phenotype, consistent with stage III NK progenitors. Like freshly isolated SLT stage III cells, HSC-derived NK22 cells express NKp44, CD161, CCR6, IL1 receptor, AHR, and ROR-γτ. IL-1β and IL-23 stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 17 publications
5
60
1
Order By: Relevance
“…Thus, the expression of LFA-1 marks CD161 + CD56 + CD117 − CD7 + NK cells at late stages of differentiation (expression of CD94/NKG2A, and NCR, IFN-γ production and cytolytic granules). On the other hand, the LFA-1 − fraction (CD161 + CD56 + CD117 +/− CD7 − LFA-1 − CD94/NKG2A − ) is heterogeneous and may contain both conventional NK-cell precursors and ILC3-like cells [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the expression of LFA-1 marks CD161 + CD56 + CD117 − CD7 + NK cells at late stages of differentiation (expression of CD94/NKG2A, and NCR, IFN-γ production and cytolytic granules). On the other hand, the LFA-1 − fraction (CD161 + CD56 + CD117 +/− CD7 − LFA-1 − CD94/NKG2A − ) is heterogeneous and may contain both conventional NK-cell precursors and ILC3-like cells [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in vitro models of human NK-cell development from umbilical cord blood (UCB) derived CD34 + cells have shown that either NK-or ILC3-cell differentiation can be obtained [26][27][28]. Thus, the expression of LFA-1 marks CD161 + CD56 + CD117 − CD7 + NK cells at late stages of differentiation (expression of CD94/NKG2A, and NCR, IFN-γ production and cytolytic granules).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sequential process of cell marker acquisition identifies NK cell precursor intermediates with different functional properties Grzywacz et al, 2006 Tang et al, 2011). The production of CXCL8 could have a role in the modulation of hematopoietic cell lineage commitment.…”
Section: Acquisition Of Nk Cell Receptors and Functionmentioning
confidence: 99%